Malnutrition in adult patients treated with venoarterial extracorporeal membrane oxygenation: A descriptive cohort studyCentral MessagePerspective - Stacy Pelekhaty, MS, RDN, LDN; Julie Gessler, RDN, LDN; Devon Baer, RDN, LDN; Raymond Rector, CCP; Michael Plazak, PharmD, BCCP; Allison Bathula, PharmD, BCCP; Chris Wells, PhD, PT, CCS, FCCM; Aakash Shah, MD; Alison Grazioli, MD; Bradley Taylor, MD; Bartley P. Griffith, MD; Joseph Rabin, MD (JTCVS Open)
Objective: To evaluate malnutrition and its association with outcomes in adult patients requiring venoarterial (VA) extracorporeal membrane oxygenation (ECMO). Methods: Patients cannulated for VA ECMO between January 1, 2020, and January 1, 2023, were screened. Patients on ECMO for <48 hours or without a nutritional evaluation were excluded. Demographic and anthropometric data were collected retrospectively. Malnutrition assessments were conducted using the Global Leadership Initiative on Malnutrition framework. Outcomes analyzed were duration of ECMO and in-hospital mortality. Patients were stratified by admission and discharge nutritional status for analysis. Baseline characteristics were controlled for with propensity score matching. Results: Data from 197 patients was analyzed. The cohort was 68% male. The median duration of ECMO was 139.5 hours (interquartile range [IQR], 94.8-257 hours), and mortality was 35%. Thirty-three patients presented with malnutrition, and 61 developed hospital-acquired malnutrition, for an incidence of 47.7%. Malnutrition at any point was associated with longer duration of ECMO (median, 180 hours [IQR, 107.8-335.8 hours] vs 120 hours [IQR, 90-185.8 hours]; P < .001). Patients with hospital-acquired malnutrition required a 50% longer duration of ECMO (median, 182.5 hours [IQR, 101.5-367 hours] vs 123 hours [IQR, 90.8-211.5 hours]; P < .001). Preexisting malnutrition was associated with a nonsignificant increase in mortality (48.2% vs 32.9%; P = .13), which was similar after 3:1 propensity score matching (43.3% vs 35.4%; P = .44). Conclusions: In adult patients, malnutrition appears to be associated with prolonged duration of VA ECMO. Adequately powered studies are needed to further investigate the relationship between malnutrition and mortality.